LINGKUNGAN SEKOLAH SEBAGAI INSPIRASI VISUAL ANAK DALAM BERKARYA SENI RUPA - Anung Pradipta Anung Pradipta; Deni Setiawan Deni Setiawan (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
ABSTRACT The utilization of the school environment as a visual inspiration source in elementary school art learning has not been fully optimized because the learning process still relies heavily on picture examples from books and teacher instructions. As a result, students have limited opportunities to observe and explore real objects in their surroundings. This study aimed to describe the role of the school environment as a source of children’s visual inspiration in creating artworks among fourth-grade students at SD Negeri Slawi Wetan 03. The research employed a qualitative method with a descriptive approach. The participants consisted of the principal, the fourth-grade teacher, and 19 students, while interviews were conducted with four students selected through purposive sampling. Data were collected through observation, semi-structured interviews, documentation, and students’ artworks. The data were analyzed using Thematic Data Analysis. The findings revealed that the school environment, including buildings, schoolyards, trees, gardens, fences, classrooms, and the overall school atmosphere, provided direct visual experiences that helped students generate drawing ideas. Students used observations of colors, shapes, sizes, and environmental details as visual references before creating artworks. Although observing the same environment, students produced diverse artworks in terms of composition, colors, and imaginative elements. These findings indicate that the school environment contributes to the development of students’ creativity, observation skills, imagination, and artistic expression in elementary school art learning. ABSTRAK Pemanfaatan lingkungan sekolah sebagai media inspirasi visual dalam pembelajaran seni rupa di sekolah dasar masih kurang maksimal karena proses pembelajaran lebih sering menggunakan contoh gambar dari buku maupun arahan guru. Kondisi tersebut menyebabkan kesempatan siswa untuk mengamati dan mengeksplorasi objek nyata di sekitar sekolah menjadi terbatas. Penelitian ini bertujuan untuk mendeskripsikan peran lingkungan sekolah sebagai sumber inspirasi visual anak dalam berkarya seni rupa pada siswa kelas IV SD Negeri Slawi Wetan 03. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Subjek penelitian meliputi kepala sekolah, guru kelas IV, dan 19 siswa, sedangkan wawancara dilakukan kepada empat siswa yang dipilih melalui teknik purposive sampling. Pengumpulan data dilakukan melalui observasi, wawancara semi-terstruktur, dokumentasi, serta hasil karya siswa. Data dianalisis menggunakan Thematic Data Analysis. Hasil penelitian menunjukkan bahwa lingkungan sekolah, seperti gedung, halaman, pepohonan, taman, pagar, ruang kelas, dan suasana sekolah, mampu memberikan pengalaman visual secara langsung yang memudahkan siswa menemukan ide menggambar. Siswa memanfaatkan hasil pengamatan terhadap warna, bentuk, ukuran, dan detail objek lingkungan sebagai acuan visual sebelum membuat karya. Walaupun mengamati objek yang sama, karya yang dihasilkan siswa tetap beragam dari segi komposisi, warna, maupun unsur imajinatif. Temuan penelitian ini menunjukkan bahwa lingkungan sekolah berperan dalam meningkatkan kreativitas, kemampuan observasi, imajinasi, dan ekspresi artistik siswa pada pembelajaran seni rupa di sekolah dasar.